2003
DOI: 10.1046/j.1440-1711.2003.t01-1-01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Murine dendritic cell development: Difficulties associated with subset analysis

Abstract: Summary Dendritic cells are bone marrow-derived professional antigen presenting cells that play major roles in both the induction of primary immune responses and tolerance. It has become clear that dendritic cells are a heterogenous group of cells that vary in cell surface marker expression and function. Multiple dendritic cell subsets have now been defined in mouse lymphoid organs and peripheral tissues. A knowledge of the function and relationship between dendritic cell subsets will be essential for understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 109 publications
(137 reference statements)
0
22
1
Order By: Relevance
“…CD4, CD8, and the pDC marker B220 were not identified in this population (data not shown). Taken together, this phenotypic pro- (49,50).…”
Section: Accumulated In the Lung In Response To Particulate Agindumentioning
confidence: 66%
“…CD4, CD8, and the pDC marker B220 were not identified in this population (data not shown). Taken together, this phenotypic pro- (49,50).…”
Section: Accumulated In the Lung In Response To Particulate Agindumentioning
confidence: 66%
“…Additionally, two major subtypes of CD11c ϩ DC have been described, plasmacytoid and myeloid DC. Myeloid DC are CD11c ϩ , CD11b ϩ , CD8␣ Ϫ , and B220 Ϫ (2,3,19,80), whereas plasmacytoid DC are CD8␣ ϩ and B220 ϩ and lack expression of costimulatory molecules (2,3,7,13,61,80). In preliminary studies with both naïve and infected mice, less than 3% of lung DC expressed B220 (Wozniak and Levitz, unpublished observations), suggesting that the vast majority of these DC are myeloid DC.…”
Section: Fig 4 Effect Of Infection With C Neoformans On the Percenmentioning
confidence: 99%
“…In addition, we observed that SP-D increases antigen presentation of bacterial-derived antigen by bone marrow-derived dendritic cells that subsequently and efficiently activate antigen-restricted T-cell hybridomas (CD4ϩ) to increase secretion of IL-2 (28). Dendritic cells are considered a heterogeneous cell population, and their lineage, origin, and degree of maturation are important determinants of their effect on T cells (29). Studies have also shown differences between bone marrowderived dendritic cells and dendritic cells isolated from the spleen or lymph nodes (30,31).…”
mentioning
confidence: 99%